Annealing and characterisation of CuInS2 thin films prepared on sapphire substrates by pulsed laser deposition. (July 2014) - Shang, Xunzhong; Zhang, Lei; Fang, Jingang; Li, Mingkai; He, Yunbin
Abstract : Quasi-epitaxial CuInS2 thin films were deposited on c -sapphire substrates at optimised temperature by the pulsed laser deposition method using a self-made ceramic target. Crystalline and stoichiometric CuInS2 film with a band gap energy of 1·43 eV is obtained by a post-annealing/sulphurisation process at a temperature of 500°C, which shows a highly (112) preferential orientation with a smallest full width at half maximum value of 0·19°. The as-deposited films show the coexistence of CuInS2 chalcopyrite and CuAu orderings measured by Raman spectroscopy, and a polymorphic transformation of metastable CuAu ordering into the equilibrium chalcopyrite structure takes place at the annealing temperature of 500°C with the presence of a surface segregated Cux S phase. The morphologies and compositions of the films before and after annealing are characterised by scanning electron microscopy and energy dispersive X-ray analysis.